Survival of solid cancer patients in France, 1989–2013: a population-based study. Issue 6 (November 2017) - Cowppli-Bony, Anne; Uhry, Zoé; Remontet, Laurent; Voirin, Nicolas; Guizard, Anne-Valérie; Trétarre, Brigitte; Bouvier, Anne-Marie; Colonna, Marc; Bossard, Nadine; Woronoff, Anne-Sophie; Grosclaude, Pascale
Abstract : This study provides updates of net survival (NS) estimates at 5, 10, and 15 years as well as survival trends for 35 solid cancers in France using data from 19 population-based cancer registries. The study considered all cases of solid cancer diagnosed between 1989 and 2010 in patients older than 15 years of age who were actively followed up until 30 June 2013. NS was estimated using the Pohar-Perme method. The age-standardized NS used the international cancer survival standard weights. The 5-year age-standardized NSs ranged from 4% (pleural mesothelioma) to 93% (prostate) in men and from 10% (pancreas) to 97% (thyroid) in women. The 10-year age-standardized NSs ranged from 2% (pleural mesothelioma) in both sexes to 95% (testis) in men and 91% (thyroid) in women. The most frequent cancers (namely, breast and prostate cancers) had the highest NSs: 87 and 93% at 5 years and 78 and 84% at 10 years, respectively. Several cancers (especially lung, pancreas, and liver cancer) had very poor prognoses (5-year NSs under 20%). Fifteen-year NSs remained high for testis cancer. In most cancers, 5- and 10-year age-standardized NSs increased between 1989 and 2010. Advanced age was associated with a poor prognosis and little improvement in survival. The increases in cancer survival are probably related to earlier diagnosis and therapeutic advances over the last decade. However, poor prognoses are still found in some alcohol-related and tobacco-related cancers and in elderly patients, highlighting the need for more prevention, diagnosis, and treatment efforts. Abstract : Supplemental Digital Content is available in the text.